Hubungan Adverse Childhood Experience (ACE) dengan Psychological Distress pada Mahasiswa Universitas Negeri Padang - Islami, Azizah; Rinaldi, Rinaldi (YASIN, 2024)
As a student, students are required to be able to complete the lecture level with satisfactory grades. In reality, many students are not only responsible for studying but also have other responsibilities such as organisations, work and family. Common demands experienced by students such as getting good grades, getting a job, building a career and some are also required to get married immediately. Demands that exceed the limits of the ability of students will trigger the onset of psychological distress. Psychological distress is a condition or unpleasant feeling that is felt subjectively by individuals. Distress can be caused by situational factors, namely adverse childhood experience. This study aims to determine the relationship between Adverse Childhood Experience (ACE) and Psychological Distress in Padang State University Students. This study uses quantitative research methods with a correlational approach. Sampling using purposive sampling technique with a total of 100 respondents. Data analysis using product moment correlation. The results showed that ACE and psychological distress had a positive relationship with a p value of 0, 00> 0.05 with a pearson correlation value of 0.587.